Pengaruh Kualitas Produk dan Citra Merek Hijab Zoya terhadap Gaya Hidup Postmodern Mahasiswa (Studi Kasus di Politeknik API Yogyakarta) - Fatimah, Siti (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2023)
This study aimed to determine the effect of product quality and brand image on the postmodern lifestyle of students in Yogyakarta simultaneously and partially, and to determine which product quality and brand image had the most influence on the postmodern lifestyle of students in Yogyakarta. The population and sample in this study were API Polytechnic students who were Muslim and wore hijabs. The sampling technique was by convenience sampling with a sample of 100 respondents. The instrument test used SPSS for Windows 17.0 and to test the hypothesis used multiple linear regression. The results of the study revealed that the results of the F test showed that product quality and brand image simultaneously influenced the postmodern lifestyle of students in Yogyakarta. Based on the results of the t test, product quality had a positive but not significant effect on the postmodern lifestyle of students in Yogyakarta, while brand image had a significant positive effect on their postmodern lifestyle. Brand image had the most dominant influence on the postmodern lifestyle of students in Yogyakarta.